Melioidosis parotitis in children. - Dance, D (BioMed Central, 2016)
A recent paper published in JVATiTD reporting a child in Hainan with parotitis caused by Burkholderia pseudomallei misleadingly described parotitis as a rare manifestation of melioidosis. In fact, it is one of the commonest forms of paediatric melioidosis seen in other parts of Southeast Asia, although interestingly not in Australia.